Gen Z sustainable consumption: evolution during and after COVID-19 - Nava Rogel, Rosa María (2025)
Given the power of decision and persuasion that Generation Z is acquir- ing, it is important to know the changes in the motivations they have towards sustainable consumption. This research analyzes the evolution of sustainable food consumption factors in Centennials during and after the pandemic, based on the Theory of Planned Behavior, which has been widely used to understand this phenomenon. In the first four months of 2021 and 2023, 662 young people born between 2000 and 2007 were surveyed; with the data collected, regression equations were calculated for each year, demonstrating a significant change in its structure with the Chow Test. During the pandemic and because of their young age, Gener- ation Z had fewer possibilities to decide; in the new normal they acquired more freedom, increasing their purchase intention. This longitudinal study shows that the basic postulates of the Theory of Planned Behavior are fulfilled, if individuals have decision-making power and freedom to select what they prefer.